Altered astrocytic function in experimental neuroinflammation and multiple sclerosis. Issue 6 (28th November 2020) - das Neves, Sofia Pereira; Sousa, João Carlos; Sousa, Nuno; Cerqueira, João José; Marques, Fernanda
Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) that affects about 2.5 million people worldwide. In MS, the patients' immune system starts to attack the myelin sheath, leading to demyelination, neurodegeneration, and, ultimately, loss of vital neurological functions such as walking. There is currently no cure for MS and the available treatments only slow the initial phases of the disease. The later‐disease mechanisms are poorly understood and do not directly correlate with the activity of immune system cells, the main target of the available treatments. Instead, evidence suggests that disease progression and disability are better correlated with the maintenance of a persistent low‐grade inflammation inside the CNS, driven by local glial cells, like astrocytes and microglia. Depending on the context, astrocytes can (a) exacerbate inflammation or (b) promote immunosuppression and tissue repair. In this review, we will address the present knowledge that exists regarding the role of astrocytes in MS and experimental animal models of the disease. Main points: Astrocytes lose physiological and gain pathological functions that can be beneficial or detrimental for MS. Astrocytes are a possible therapeutic target in MS. Astrocytes heterogeneity is observed between humans and rodent/non‐human primates.